The mechanical behavior of polylactic acid (PLA) films: fabrication, experiments and modelling - Mirkhalaf, S. M.; Fagerström, M. (Mechanics of time-dependent materials, 2021)
Polylactic acid (PLA) is one of the highly applicable bio-polymers in a wide variety of applications including medical fields and packaging. In order to quantitatively model the mechanical behavior of PLA and PLA based bio-composite materials, and also tailor new bio-composites, it is required to characterize the mechanical behavior of PLA. In this study, thin films of PLA are fabricated via hot-pressing, and tensile experiments are performed under different strain rates. To model the mechanical behavior, an elasto-viscoplastic constitutive model, developed in a finite strain setting, is adopted and calibrated. Using the physically-based constitutive model, all regimes of deformation under uniaxial stress state, including post-yield softening, were adequately captured in the simulations. Also, the rate dependency of the stress–strain behavior was properly modelled.